The life history of Ostrocerca dimicki (Frison) in a short-flow, summer-dry Oregon stream - Stewart, Kenneth W. (Illiesia, 2010)
The voltinism and life history of Ostrocerca dimicki (Frison) were determined from monthly benthic collections of larvae, and adults from an emergence trap,from a short-flow, intermittent stream. Collections were from four water years, 1996-97, 1997-98, 1998-99, and 2002-03, selected from 17 years of samples. Determination of emergence timing was supplemented by collections of adults in 2008, from 10 emergence traps set to include a range of habitat types on the receiving seasonal stream. Growth was assessed by increase of head- capsule width of 667 larvae. A total of 202 males and 261 females were taken in the 4-year and 2008 emergence trap samples. Emergence in late February- April, first appearance of early- instar larvae the following December or January about a month after typical resumption of water flow, and rapid growth in 3-4 months, indicated a straightforward univoltine, fast cycle, with a probable over-summer egg diapause. Population levels fluctuated substantially over the 17-year period, depending on rainfall and duration of flow. Drought periods reduced the population, leading to low or no emergence and subsequent slow recovery, presumably from long-term diapausing eggs.
Keywords: entomology; Ostrocerca; life history; Nemouridae; Oregon; Plecoptera